Statin Use in Prostate Cancer: An Update - Babcook, Melissa A. (Nutr Metab Insights, 2016)
3-Hydroxy-3-methylglutaryl-coenzyme A reductase inhibitors, known as statins, are commonly prescribed for the treatment of hypercholesterolemia and cardiovascular disease. A systematic review was conducted using the keywords “statin and prostate cancer” within the title search engines including PubMed, Web of Science, and the Cochrane Library for relevant research work published between 2004 and December 2015. Although still premature, accumulating clinical evidence suggests that statin use may be beneficial in the prevention and/or treatment of prostate cancer. These human studies consist of meta-analyses of secondary endpoints obtained from randomized, controlled cardiovascular disease clinical trials of statins, patient database, observational studies, and a few, small case–control studies, directly addressing statin use on prostate cancer pathology and recurrence. This review summarizes and discusses the recent clinical literature on statins and prostate cancer with a recommendation to move forward with randomized, placebo-controlled clinical trials, investigating the use of statins. Additional preclinical testing of statins on prostate cancer cell lines and in vivo models is needed to elucidate pathways and determine its efficacy for prevention and/or treatment of prostate cancer, more specifically, the difference in the effectiveness of lipophilic versus hydrophilic statins in prostate cancer.